Teachers’ Perception on The Use of Teaching Media in English Classroom at Madrasah Diniyah Putri - Astuti, Missi Tri; Suprayetno, Edi; Shawati, Shawati; Raihana, Esti (Institut Agama Islam Negeri Palopo, 2023)
This study was aimed to investigate teachers' perspectives on the utilization of teaching media in English classrooms at Madrasah Alyah Diniah Putri. The method used in this study was qualitative method. The participants were 10 English teachers from Madrasah Alyah Diniah Putri. The data for this study was collected by using questionnaire which consisted of 15 items. The data analysis used analytical model proposed by (Miles, M. B., Huberman, A. M., & Saldana, J., 2013). The research explored the significances of English teaching media, the criteria for appropriateness, commonly used types of media, obstacles in implementation, and the process of creating teaching media based on student needs. Findings revealed that teachers acknowledge the crucial role of media in facilitating effective learning experiences, emphasizing interactivity, practicality, and alignment with students' characteristics. WhatsApp Group emerges as the dominant medium, though challenges in facilities, resources, and technical aspects are evident. Adaptability of teachers and students in overcoming obstacles is noted. The study underscores the importance of needs analysis and learning objectives in creating tailored teaching media. Overall, the research provides insights for educators, policymakers, and researchers, guiding effective practices in integrating teaching media into English language classrooms. Keywords: English Classroom; Teaching Media; Teachers’ Percetion